Preparation and properties of poly(lactic acid)/cellulose nanocrystals nanocomposites compatibilized with maleated poly(lactic acid). Issue 9 (23rd February 2017) - Chen, Jian; He, Hui; Yu, Peng; Jia, Yunchao; Meng, Shuna; Wang, Jingyuan
Abstract : High thermally stable cellulose nanocrystals (CNCs), prepared by acid hydrolysis, were obtained by combination of alkali treatment (label as CNCs) and mixing with poly(ethylene oxide) (PEO). Dry mixture of PEO/CNCs (oCNCs) was subsequently introduced into poly(lactic acid) (PLA) matrix by melt extrusion and then compatibilizing with maleated PLA. The effects of compatibilization with maleated PLA (PLA‐g‐MAH) on the structure and properties of PLA/PEO/CNCs nanocomposites were investigated. PLA/PEO/CNCs/PLA‐g‐MAH nanocomposites displayed improved interfacial adhesion as compared to PLA/PEO/CNCs composites. Differential scanning calorimetry analysis showed enhanced crystallization ability for the resulting nanocomposites. The significant enhancement of thermal stability and tensile parameters, as strength and elongation at break were observed for the composites, which was primarily attributed to strong interfacial adhesion between filler and matrix and the uniform dispersion of CNCs. POLYM. COMPOS., 39:3092–3101, 2018. © 2017 Society of Plastics Engineers